Dynamic Assembly of Viscoelastic Networks by Aqueous Liquid-Liquid Phase Separation and Liquid-Solid Phase Separation (AqLL-LS PS2 ) - Cui, Huanqing (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.